Protective effect of sulphated polysaccharide from Padina tetrastromatica (Dictyotaceae) on thromboembolism - Mohsin, Sulaiman; Mahadevan, R; Sumayya, A.S.; Kurup, G. Muraleedhara (Journal of Ecobiotechnology, 2015)
Even though anti thrombotic effects have been reported with polysaccharides isolated from various marine algae of dictyotaceae, containing uronic acid as the main constituent. But a new polysaccharide was isolated from a species of marine algae from the Kerala coast with a composition different from those reported so far. The antiplatelet and antithrombotic activities of polysaccharides from Padina tetrastromatica were investigated on platelet aggregation in vitro and on pulmonary thrombosis in vivo. The polysaccharide fractions showed concentration dependent inhibitory effects on ADP-induced platelet aggregation. Using an in vivo mouse thrombotic model in which mice were challenged with an intravenous injection of collagen and epinephrine mixture, oral administration of the polysaccharide prior to the injection produced a significant inhibition of thrombotic death or paralysis. Aspirin showed a significant inhibition of thrombotic death similar to polysaccharide of higher dose. Polysaccharide fractions showed significant prolongation of mouse tail bleeding time. The present findings showed clear evidence of protection against thromboembolism and had good antithrombotic activity. Available data obtained by in vitro models suggest that there is a correlation between the sulfate content and antithrombotic activity.